International Mechanism of the Environmental Information Access and Cooperation Framework for Climate Change Protection - Ladychenko, Viktor; Melnychuk, Olha; Julia Kanaryk, Olena Yara (European Journal of Sustainable Development, 2019)
Climate change and global warming are challenging for humanity. International cooperation and the formation of joint approaches to solving global challenges are of paramount importance for sustainable development. Like many countries in the region, Ukraine threatens to increase the number of natural disasters, floods in the Carpathians, transformation southern region steppe into the desert, flooding coastal parts and a shortage of drinking water in the central and eastern regions. Thus, this study explores the international mechanism of the environmental information access as a complex multi-level system, which determines various types of international cooperation. Environmental information access is of great practical importance both for humanity as a whole and for further reformation of the legislation of individual countries in order to ensure sustainable development, as well as to improve the practical activities of civil society. The findings show the need for people`s lifestyle changes, their environmental education and work. We therefore propose the international mechanism of the environmental information access as cooperation framework which enables companies and business communities more effectively and creatively solve economic and social problems. Keywords: Environmental information, information human rights, sustainable development, EU environmental policy, environmental human rights